PENGARUH RISIKO BISNIS, KINERJA KEUANGAN DAN KINERJA LINGKUNGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2020 - Nona Jane Onoyi; One Yantri; Ely Kurniawati; Diana Titik Windayati; Nona Jane Onoyi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The purpose of this study was to determine the effect of business risk, financial performance, and environmental performance on the stock price. This study uses business risk, financial performance proxied by ROA, and environmental performance proxied by PROPER as independent variables. Meanwhile, the stock price is the dependent variable. The research population is a coal mining company listed on the IDX as many as 22 companies. The research sample took 11 companies obtained by using the purposive sampling method. The research sample took 11 companies obtained by using the purposive sampling method. The research method uses multiple linear regression. The results showed that partially the business risk variable had no significant effect on stock prices, while the financial performance and environmental performance variables had a significant effect on stock prices. Simultaneously the variables of business risk, financial performance, and environmental performance have a significant effect on the stock price. Advice for the company is to maintain financial performance and environmental performance in order to maintain investor confidence in the company.